The Challenge of a “Functional Cure” for AIDS by Gene Modified HSCT Therapy - Xu, Lei; Chen, Hu; Zhang, Bin (Current Stem Cell Research & Therapy, 2015)
Acquired immunodeficiency syndrome (AIDS), an infectious disease which is difficult to be cured, is regularly and effectively treated with anti-retroviral therapy in clinic. When considering about the defects of antiretroviral therapy (ART), patients need a new way to cure AIDS. With the development of genetic engineering technology and humanized mouse models, a new way has been found to achieve a “functional cure” for AIDS. One/some specific gene(s), such as CCR5 and CXCR4, can be knocked out to produce HIV-resisting cells, so as to achieve the purpose of curing AIDS. To find a safe and effective therapy for AIDS, treatment strategy and technical scheme should be improved and optimized in many aspects. Moreover, different stages of works have been done in laboratory and in clinic based on this gene mutation strategy. However, a great deal of challenge has emerged while great progress has been made. Safety considerations and effectiveness of gene modified stem cell in clinic are major obstacles of the application of this strategy.
Keywords: CCR5/CXCR4